Telescopical?

Calculus Level 3

r = 1 cot 1 ( 3 r 2 5 12 ) \large \displaystyle \sum _{r=1} ^{\infty }\cot ^{-1} \left(3r^2-\frac {5}{12}\right)

If the above summation can be expressed as cot 1 A \cot^{-1}{A} , enter your answer as 4 A 4A .


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Parth Sankhe
Dec 13, 2018

Important identities: cot 1 x = tan 1 1 x \cot^{-1} x = \tan^{-1} \frac {1}{x} ; tan 1 = π 2 \tan ^{-1} ∞ =\frac {π}{2} ; tan 1 x + cot 1 x = π 2 \tan^{-1} x + \cot^{-1} x =\frac {π}{2}

The series is = tan 1 12 36 r 2 5 =\tan^{-1} \frac {12}{36r^2-5}

Dividing by 4,

= tan 1 3 1 + ( 9 r 2 9 4 ) =\tan ^{-1} \frac {3}{1+(9r^2-\frac {9}{4})}

= tan 1 ( 3 r + 1.5 ) ( 3 r 1.5 ) 1 + ( 3 r + 1.5 ) ( 3 r 1.5 ) = tan 1 ( 3 r + 1.5 ) tan 1 ( 3 r 1.5 ) =\tan ^{-1} \frac {(3r+1.5)-(3r-1.5)}{1+(3r+1.5)(3r-1.5)}=\tan ^{-1} (3r+1.5)- \tan ^{-1} (3r-1.5)

This would form a telescopic series, where each term will be cancelled out by the following terms, leaving only tan 1 tan 1 ( 1.5 ) = cot 1 1.5 \tan ^{-1} ∞ - \tan ^{-1} (1.5) = \cot ^{-1} 1.5

Chew-Seong Cheong
Dec 14, 2018

Relevant wiki: Writing a Proof by Induction

If we defined S n = r = 1 n cot 1 ( 3 r 2 5 12 ) \displaystyle S_n = \sum_{r=1}^n \cot^{-1} \left(3r^2-\frac 5{12}\right) , where n n is a positive integer, then we find that S n = cot 1 ( 13 12 n + 3 2 ) S_n = \cot^{-1} \left(\dfrac {13}{12n} + \dfrac 32\right) . Let us prove by induction that the claim is true for all n 1 n \ge 1 .

For n = 1 n=1 , S 1 = cot 1 ( 3 ( 1 2 ) 5 12 ) = cot 1 ( 31 12 ) = cot 1 ( 13 12 ( 1 ) + 3 2 ) S_1 = \cot^{-1} \left(3(1^2) - \dfrac 5{12}\right) = \cot^{-1} \left(\dfrac {31}{12}\right) = \cot^{-1} \left(\dfrac {13}{12(1)} + \dfrac 32 \right) . The claim is true for n = 1 n=1 .

Assuming the claim is true for n n , then

S n + 1 = S n + cot 1 ( 3 ( n + 1 ) 2 5 12 ) = cot 1 ( 13 12 n + 3 2 ) + cot 1 ( 3 ( n + 1 ) 2 5 12 ) = cot 1 ( 18 n + 13 12 n ) + cot 1 ( 36 ( n + 1 ) 2 5 12 ) = cot 1 ( 18 ( n + 1 ) 5 12 n ) + cot 1 ( 36 ( n + 1 ) 2 5 12 ) = cot 1 ( 18 ( n + 1 ) 5 12 n × 36 ( n + 1 ) 2 5 12 1 18 ( n + 1 ) 5 12 n + 36 ( n + 1 ) 2 5 12 ) = cot 1 ( 648 ( n + 1 ) 3 180 ( n + 1 ) 2 234 ( n + 1 ) + 169 432 ( n + 1 ) 3 432 ( n + 1 ) 2 + 156 ( n + 1 ) 2 ) = cot 1 ( 3 2 + 13 12 ( n + 1 ) ) \begin{aligned} S_{n+1} & = S_n + \cot^{-1} \left(3(n+1)^2 - \frac 5{12}\right) \\ & = \cot^{-1} \left(\frac {13}{12n} + \frac 32\right) + \cot^{-1} \left(3(n+1)^2 - \frac 5{12}\right) \\ & = \cot^{-1} \left(\frac {18n + 13}{12n} \right) + \cot^{-1} \left(\frac {36(n+1)^2 - 5}{12}\right) \\ & = \cot^{-1} \left(\frac {18(n +1)-5}{12n} \right) + \cot^{-1} \left(\frac {36(n+1)^2-5}{12}\right) \\ & = \cot^{-1} \left(\frac {\frac {18(n +1)-5}{12n} \times \frac {36(n+1)^2-5}{12} -1}{\frac {18(n +1)-5}{12n} + \frac {36(n+1)^2-5}{12}} \right) \\ & = \cot^{-1} \left(\frac {648(n+1)^3-180(n+1)^2-234(n+1)+169}{432(n+1)^3-432(n+1)^2+156(n+1)^2}\right) \\ & = \cot^{-1} \left(\frac 32 + \frac {13}{12(n+1)}\right) \end{aligned}

Showing that the claim is also true for n + 1 n+1 , therefore, it is true for all n 1 n \ge 1 .

Now we have lim n S n = lim n cot 1 ( 13 12 n + 3 2 ) = cot 1 3 2 \displaystyle \lim_{n \to \infty} S_n = \lim_{n \to \infty} \cot^{-1} \left(\frac {13}{12n} + \frac 32\right) = \cot^{-1} \frac 32 . 4 A = 4 × 3 2 = 6 \implies 4A = 4 \times \dfrac 32 = \boxed 6 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...